Entrepreneurial Leadership: Inspiring Leadership Values in Building Excellent Vocational High Schools - Agustin Hanivia Cindy; Sugiyono Sugiyono; Husaini Usman (International Journal of Education, Vocational and Social Science, 2022)
This study examines leadership values ​​that inspire in building superior vocational high schools, including creative, innovative, proactive, risk taking, communicative, motivational, personal, and strategy. This type of research is a case study where data is collected through in-depth interviews, direct observation, document analysis, and observation of audio visual material. The analysis was carried out by making transcriptions of data, notes, video recordings, and documents; generate ideas, codify data, design themes and interpret data. The results show that entrepreneurial leadership has a positive effect on the performance of leaders. This article is expected to be a guide for school principals in obtaining and practicing inspiring entrepreneurial leadership values ​​to increase the effectiveness of their schools and to facilitate the process of a quality school. Regarding the results, this study implies that inspiring leadership serves as one of the key factors for building excellent vocational high schools. However, due to the limitations of this study, further research is needed.